2022
DOI: 10.1016/j.addbeh.2022.107247
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and drinking to cope in the early COVID period: Data from the 2019–2020 US National Alcohol Survey

Abstract: Background Studies show drinking to cope and mental health problems have increased during the COVID-19 pandemic, however, their samples have been limited by convenience sampling or lack of a pre-pandemic measure. We examined the early impact of the COVID-19 pandemic on mental health, drinking to cope and their association using a probability-based sample of the US adult population. Methods Data was drawn from the probability samples of the 2019-2020 National Alcohol Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
0
19
0
1
Order By: Relevance
“…Fifty-three percent of the prevalence points (n = 47) included in this review were collected within the first four months of the pandemic ( Table 2 ). The average number of days between last day of data collection and date of article publication was 205 days, with the shortest number of days being 45 ( Czeisler, 2020 ) and the longest number of days being 634 ( Martinez et al, 2022 ). Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-three percent of the prevalence points (n = 47) included in this review were collected within the first four months of the pandemic ( Table 2 ). The average number of days between last day of data collection and date of article publication was 205 days, with the shortest number of days being 45 ( Czeisler, 2020 ) and the longest number of days being 634 ( Martinez et al, 2022 ). Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these factors may be more prominent in certain subgroups. For example, studies have found that level of alcohol problems was associated with loneliness only for women ( 38 ), and significant associations between early-COVID-19 period, depression and anxiety symptoms, and drinking to forget one's worries among women only ( 39 ). Research also found higher psychological distress among young adults aged 18–24 years and Hispanic/Latino individuals during the pandemic ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that depression and anxiety levels peak at similar times as COVID-19 cases [ 7 ]. Finally, others have found that pandemic-associated distress was also associated with problematic alcohol consumption [ 31 , 32 ]. For example, Gilley et al [ 33 ] found that alcohol consumption was associated with COVID-19 positivity.…”
Section: Discussionmentioning
confidence: 99%